Estudi de les fonts d'una Epistula de amore d'Antonio Beccadelli adreçada al valencià Francesc de Centelles (1437-1442) sobre la «vis, aut potestas» de l'amor. - HERNÀNDEZ, RUBÉN GALERA (Scripta)
The expansionist policy of the Crown of Aragon towards the Italian Mezzogiorno, headed by Alfons el Magnànim during the first half of the fifteenth century, supposed that the monarch would form around him a court of Italian humanists for the written testimony of his enterprise and the transmition to the court of the knowledge of the great Latin and Greek classical authors. This list of letters written in Greco-Latin studies, in which we find Lorenzo Valla, Guiniforte Barzizza, Bartolomeo Facio and Antonio Beccadelli (Panormita), among others, were always in contact with members of the Royal Chancery and the nobility. One of these nobles was the Valencian knight, chamberlain, counselor and marshal, Francesc-Gilabert de Centelles i Queralt, otherwise known as Ramon de Riu-sec, lord of Nules and Count of Oliva (1449), who corresponded with Barzizza and Beccadelli, to ask for advice about the nature of love. In this article, we have studied the sources of reference that Panormita consulted when writing the epistle and we contextualize it with the loving reality of the Valencian knight.